A MODEL OF COMMUNITY-BASED RURAL TOURISM PRODUCTS DEVELOPMENT - Adikampana, I Made; Sunarta, I Nyoman; Kerti Pujani, Ni Luh (Jurnal IPTA (Industri Perjalanan Wisata); Vol 7 No 1 (2019): Jurnal IPTA (July 2019), 2019)
The local community always took for granted the establishment of a tourist village as a rural tourism product. Likewise prevailed in Pinge Tourism Village, Tabanan Regency, Bali. In the context of developing rural tourism products in the Pinge Tourism Village, the participation of local communities is required to ensure the sustainability of tourism in rural areas. This paper aims to build a model for developing local community-based rural tourism products in Pinge Tourism Village. Community-based tourism (CBT) approaches are used to formulate models for rural tourism product development. The required data is collected through observation and interviews and then analyzed descriptively. The results of the analysis indicate local community-based rural tourism products are tourist pull factors in rural areas in the form of environmental characteristics and the practice of rural communities. The uniqueness of rural character and rural community routines are tourism capital posses by local communities. In addition to physical and socio-cultural uniqueness, rural tourism products are also determined by conformity with the target market. The existence of this rural tourism product model can increase local community participation in decision making and sharing of tourism benefits.